2nd Plasma Nanotechnologies and Bioapplications Workshop Scientific Program & Book of Abstracts - Galmiz, Oleksandr; Štěpánová, Vlasta; Krumpolec, Richard; Sihelník, Slavomír; Kováčik, Dušan (Masaryk University Press, 2021)
Title in English: 2. ročník workshopu Plazmové nanotechnologie a bioaplikace The Book of Abstracts contains the contributions for presentations during the 2nd Plasma Nanotechnologies and Bioapplications Workshop held on 11st - 14th October 2021 in Broumov. Workshop was attended by the researcher teams from Department of Physical Electronics(CEPLANT), Faculty of Science, Masaryk University in Brno, and Department of Experimental Physics, Faculty of Mathematics, Physics and Informatics, Comenius University in Bratislava. Within the workshop the contributions from the following four topics: Surface Modification; Bioapplications; Flexible and Printed Electronics; New Materials & New Challenges were presented in the form of oral presentations.